A nice surprise: Sacrifice expectations and partner appreciation in romantic relationships. (February 2020) - Zoppolat, Giulia; Visserman, Mariko L.; Righetti, Francesca
Romantic partners regularly encounter conflicts of interests and sacrifice their self-interest for their partner or the relationship. But is this relationship maintenance behavior always appreciated by the partner receiving the sacrifice? We examined whether expectations of sacrifices (i.e., beliefs that sacrifices are necessary, normal, and expected in relationships) predict people's appreciation for their partner and, ultimately, their relationship satisfaction. Utilizing a daily experience procedure among romantic couples in the Netherlands ( N = 253 individuals), we found that when participants perceived a partner's sacrifice, they experienced greater partner appreciation (i.e., gratitude and respect) and, in turn, felt more satisfied with their relationship when their sacrifice expectations were low, rather than high. In contrast, perceiving a partner's sacrifice had no effect on appreciation and relationship satisfaction when the sacrifice recipient held strong sacrifice expectations. These findings illustrate the power that expectations have in influencing the receiver's appreciation of their partner's pro-social behavior.